Evidences of the establishment of Cephalonomia stephanoderis and Prorops nasuta (Hymenoptera: Bethylidae) in coffee plantations in the department of Nariño, Colombia - QUINTERO-H., CLAUDIA; BUSTILLO-P., ALEX E.; BENAVIDES-M., PABLO; CHAVES-C., BERNARDO (Revista Colombiana de Entomología, 1998)
During 1996 the establishment and dispersion of Cephalonomia stephanoderis (Betrem) and Prorops nasuta (Waterston) parasitoids of the coffee berry borer (cbh), Hypothenemus hampei (Ferrari), in Sandoná, Consacá, and Ancuya, Department of Nariño, Colombia was evaluated. Farms, where parasitoids were released between 1991 and 1993, were randomly chosen and plots nearby these farms where parasitoids were not released were selected additionally. From each farm or piot a random sample of infested berries by cbb was taken, to determine by dissection the presence or absence and species of parasitoids attacking the cbb. The variables evaluated were the infestation of the cbb in the field, parasitism of C. stephanoderis and P nasuta. Information was also gathered on altitude above sea level of the plots and management practices to control cbb. Analysis of information was made by descriptive statistics and was complemented with multiple correspondence analysis and crossed tables. During the main harvest period, C. stephanoderis was found in 27.3 % of the farms where they were released and in 10% of the nearby farms, while P nasuta was found in 72.7% of the sampled farms and in 52.5% of the nearby plots. Parasitism of C. stephanoderis varied from 0.25 to 1.25% and between 0.23 and 8.25 % to P nasuta. Fifty-seven percent of the initially selected farms were evaluated again in the next minor harvest period; results showed that C. stephanoderis was found in 13,8% and P nasuta in 44,82% of the plots, with parasitism from 0.2 to 0.94% and from 0.1 to 5.4% respectively. Both evaluations made evident the establishment of these parasitoids; howPver, P. nasuta was recCaféovered more frequently than C. .stephanoderis. The abundance of these parasitoids may have been affected by farms with low cbb infestations (< 10%) and control practices such as cultural control, Beauveria bassiana (Balsamo) Vuillemin, and sprays of chemical insecticides against cbb populations.